Current state of NK cell-mediated immunotherapy in chronic lymphocytic leukemia - Wang, Zong-Han; Li, Wei; Dong, Hao; Han, Fujun (Frontiers in Oncology, 2023)
Chronic lymphocytic leukemia (CLL) has become one of the most common hematological diseases in western countries, with an annual incidence of 42/100,000. Conventional chemotherapy and targeted therapeutic drugs showed limitations in prognosis or in efficiency in high-risk patients. Immunotherapy represented is one of the most effective therapeutic approaches with the potential of better effect and prognosis. Natural killer (NK) cells are good options for immunotherapy as they can effectively mediate anti-tumor activity of immune system by expressing activating and inhibiting receptors and recognizing specific ligands on various tumor cells. NK cells are critical in the immunotherapy of CLL by enhancing self-mediated antibody-dependent cytotoxicity (ADCC), allogeneic NK cell therapy and chimeric antigen receptor-natural killer (CAR-NK) cell therapy. In this article, we reviewed the features, working mechanisms, and receptors of NK cells, and the available evidence of the advantages and disadvantages of NK cell-based immunotherapies, and put forward future study directions in this field.